PEMANFAATAN CLOUD COMPUTING UNTUK PENGELOLAAN ADMINSTRASI SEKOLAH MENGGUNAKAN METODE NEXTCLOUD - Dwiyatno, Saleh; Wiji Wahyuningrum, Rita; Krisnaningsih, Erni; ., Rahmat; Dedi Jubaedi, Ahmad (Universitas Serang Raya, 2024)
In this modern era, technological developments are growing rapidly, one of which is in the field of education. By taking advantage of this technological development, education uses a storage technology connected to a computer and requires changes in the development and management of administrative systems. However, computers have storage limitations that affect the performance of the computer. Currently, cloud computing technology is one of the solutions to improve the efficiency and effectiveness of administrative management in the educational environment. NextCloud is one of the cloud computing applications that can be used as cloud storage to facilitate data management in an educational environment. Therefore, this research aims to process administrative data easily, flexibly and without limitations that can be accessed offline through the local network of SMKN 7 Kota Serang or online outside the network of SMKN 7 Kota Serang. The data collection technique in this research is observation. The result of this research is the construction of a cloud computing server using the nextcloud application, which has stability performance in the process of downloading and uploading data, flexible access and unlimited, which can be accessed offline through the local network of SMKN 7 Kota Serang or online outside the SMKN 7 Kota Serang network as well as good access speed and security..